Best practice in digital orthopaedics - Agnieszka Halm-Pozniak; Christoph H Lohmann; Luigi Zagra; Benedikt Braun; Max Gordon; Bernd Grimm (EFORT Open Reviews, 2023)
Digitization in orthopaedics and traumatology is an enormously fast-evolving field with numerous players and stakeholders. It will be of utmost importance that the different groups of technologists, users, patients, and actors in the healthcare systems learn to communicate in a language with a common basis. Understanding the requirements of technologies, the potentials of digital application, their interplay, and the combined aim to improve health of patients, would lead to an extraordinary chance to improve health care. Patients' expectations and surgeons’ capacities to use digital technologies must be transparent and accepted by both sides. The management of big data needs tremendous care as well as concepts for the ethics in handling data and technologies have to be established while also considering the impact of withholding or delaying benefits thereof. This review focuses on the available technologies such as Apps, wearables, robotics, artificial intelligence, virtual and augmented reality, smart implants, and telemedicine. It will be necessary to closely follow the future developments and carefully pay attention to ethical aspects and transparency.